Ações para a melhoria da qualidade do leite - Corbucci, Flavio Sader [UNESP]; Grassi, Thiago Luis Magnani [UNESP]; Ponsano, Elisa Helena Giglio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Data collected by the Ministry of Agriculture, Livestock and Supply (MAPA) concerning the quality of raw milk produced in Brazil nearly 10 years after the implementation of Instruction No. 51 of 2002 (BRAZIL, 2002) indicated that the identity and quality standards recommended by the then current legislation were not being met. So in late 2011, MAPA published Normative Instruction No. 62 (IN 62), approving a new technical regulation identity and quality of refrigerated raw milk and the technical regulation of the collection of raw milk and its refrigerated bulk transport ( BRAZIL, 2011). Data provided by previous extension projects indicated the farmer’s lack of education as the main cause of the inadequacy of the quality of milk to legal parameters. This study aimed to carry out a survey of the quality of raw milk produced in the region of Araçatuba and had the participation of 10 small producing properties of milk. Additionally, it aimed to provide instructions to farmers in obtaining milk within the legal quality standards and assess whether there was an improvement in product quality during the project period.

Os dados coletados pelo Ministério da Agricultura, Pecuária e Abastecimento (MAPA) a respeito da qualidade do leite cru produzido no Brasil quase 10 anos após a implementação da Instrução Normativa nº 51 de 2002 (BRASIL, 2002) indicaram que os padrões de identidade e qualidade preconizados pela legislação então vigente não vinham sendo cumpridos. Por isso, no final de 2011, o MAPA publicou a Instrução Normativa nº 62 (IN 62), aprovando um novo regulamento técnico de identidade e qualidade de leite cru refrigerado e o regulamento técnico da coleta de leite cru refrigerado e seu transporte a granel (BRASIL, 2011). Dados fornecidos por projetos de extensão anteriores indicaram a falta de instrução do produtor rural como a principal causa da inadequação da qualidade do leite aos parâmetros legais. Este estudo teve como objetivo realizar um levantamento da qualidade do leite cru produzido na região de Araçatuba e contou com a participação de 10 pequenas propriedades produtoras de leite. Adicionalmente, objetivou-se oferecer instruções aos produtores rurais quanto à obtenção de leite dentro dos padrões legais de qualidade e avaliar se houve melhora na qualidade do produto durante o período do projeto.
Keywords: Quality; Milk; Araçatuba; Qualidade; Leite; Araçatuba